Recommendations for stable isotope analysis of charred archaeological crop remains - Styring, Amy K.; Vaiglova, Petra; Bogaard, Amy; Church, Mike J.; Gröcke, Darren R.; Larsson, Mikael; Liu, Xinyi; Stroud, Elizabeth; Szpak, Paul; Wallace, Michael P. (Frontiers in Environmental Archaeology, 2024)
Stable isotope analysis of plant remains recovered from archaeological sites is becoming more routine. There remains a lack of consensus, however, on how to appropriately select archaeological plant remains for isotopic analysis, how to account for differences in preservation and the effect of potential contamination, and how to interpret the measured isotope values in terms of the conditions in which the plants grew. In this paper, we outline the main issues to be considered when planning and conducting an isotopic study of archaeobotanical remains. These include: 1) setting out the research question(s) that will be answerable using available analytical approaches, 2) considering the archaeological context from which plant remains derive, 3) determining appropriate sample size through consideration of estimate precision, 4) establishing the conditions in which plant remains have been preserved and potential effects on their isotope values, and 5) accounting for possible contamination during deposition. With these issues in mind, we propose some recommendations for researchers to consider when planning and conducting an isotopic study of archaeobotanical remains.